Comparison between the triamcinolone and bevacizumab subconjunctivals and changes in Interleukin-1 mRNA expression in pterygium. Issue 1 (February 2022) - Syawal, Purnamanita; Budu, Budu; Hatta, Mochammad; Massi, Muhammad Nasrum; Ichsan, Andi Muhammad; Minhajat, Rahmawati
الملخص: أهداف البحث: الظفرة هي كتلة العين الخارجية الليفية الوعائية التي تنمو من الملتحمة إلى القرنية. لم يتم التحقيق في تأثير الحقن تحت الملتحمة لتريامسينولون وبيفاسيزوماب بشكل كاف في جميع أنحاء العالم. تهدف هذه الدراسة إلى تحليل تعبير انترلوكين-١ بعد حقن تريامسينولون بيفاسيزوماب تحت الملتحمة. طرق البحث: تم تقسيم جميع المرضى بصورة عشوائية إلى ثلاث مجموعات. كل ٥ عيون في مجموعة تريامسينولون ومجموعة بيفاسيزوماب ومجموعة الدواء الوهمي. تم حقن جميع الأشخاص تحت الملتحمة قبل أسبوع واحد من الجراحة، ثم أجريت الجراحة بتقنية الطعم الذاتي. تضمنت مقاييس النتائج الرئيسية تغييرات في تعبير انترلوكين-١ حمض ريبونيوكليك المرسال بين مجموعة تريامسينولون، بيفاسيزوماب، ومجموعات الدواء الوهمي. النتائج: تم الانتهاء من جميع العينات بعد شهر واحد من المتابعة. كانت التغيرات في مستويات الدم لتعبير انترلوكين-١ حمض ريبونيوكليك المرسال في مجموعة بيفاسيزوماب ٤.٨١ ± ٠.٥٢، وكانت مجموعة تريامسينولون ٣.٤٠ ± ٢.٦٣، وكانت مجموعة الدواء الوهمي ١.٠٨± ١.٤٨، على التوالي. في المقارنة بين المجموعات، كان هناك تأثير معنوي بين مجموعة بيفاسيزوماب ومجموعة الدواء الوهمي، ٣.٧٣ ± ١.١٢، مع عدم وجود تأثير معنوي في مجموعة تريامسينولون، ١.٤٠± ١.١٢. الاستنتاجات: كان الحقن تحت الملتحمة بيفاسيزوماب وتريامسينولون قبل الجراحة فعالا في قمع الالتهاب في الظفرة. Abstract: Objectives: Pterygium is a fibrovascular external ocular mass that grows from the conjunctiva into the cornea. The effect of subconjunctival injection of triamcinolone and bevacizumab has been inadequately investigated worldwide. This study aims to analyse the expression of IL-1 after the injection of triamcinolone and bevacizumab subconjunctiva. Methods: All patients are randomized into three groups: the triamcinolone, bevacizumab group, and placebo groups, with 5 patients in each in group. All subjects are injected subconjunctivally one week before surgery, and then surgery is performed with the autograft technique. The main outcome measures include changes in the IL-1 mRNA expression between the triamcinolone, bevacizumab, and placebo groups. Results: All samples are completed after one month of follow-up. The changes in blood levels of mRNA IL-1 expression are as follows: 4.81 ± 0.52 in the bevacizumab group, 3.40 ± 2.63 in the triamcinolone group, and 1.08 ± 1.48 in the placebo group ( p  = 0.04). In the comparison between groups, there is a significant effect between the bevacizumab and placebo groups, 3.73 ± 1.12 ( p  = 0.00), with no significant effect in the triamcinolone group, 1.40 ± 1.12 ( p  = 0.06). Conclusion: The subconjunctival injection of bevacizumab and triamcinolone before surgery is effective in suppressing inflammation in pterygium.